Leg length discrepancy in total hip arthroplasty: comparison of two methods of measurement - Sayed-Noor, Arkan S. (Springer-Verlag, 2008)
Measurement of leg length discrepancy is an important part in planning a successful total hip arthroplasty (THA). Many clinical and radiological methods with variable degrees of accuracy have been advocated to carry out this measurement. We studied the accuracy of a commonly used clinical method by comparing it to a well-known and reliable radiological method. A total of 139 patients aged 44–89 (mean: 67.5 years) scheduled to undergo THA were examined for clinical and radiological leg length discrepancy measurements before and after the operation by the same observers. There was a poor correlation between the clinical and radiological methods preoperatively [r = 0.21, intra-class correlation coefficient (ICC) = 0.33]. The correlation was better postoperatively (r  = 0.45, ICC = 0.62). The clinical method used is not recommended for leg length discrepancy measurement preoperatively. Caution should even be taken when using this method postoperatively. The authors recommend using the radiological method when measuring leg length discrepancy as a part of planning for THA.